Recruitment limitation in three large‐seeded plant species in a tropical moist forest. (20th January 2022) - Garzon‐Lopez, Carol X.; Barcenas, Eduardo Medina; Ordoñez, Alejandro; Jansen, Patrick A.; Bohlman, Stephanie A.; Olff, Han
Abstract: Recruitment limitation—the failure of a species to establish recruits at an available site—is a potential determinant of plant communities' structure, causing local communities to be a limited subset of the regional species pool. Recruitment limitation results from three mechanisms: (i) lack of seed sources (i.e., source limitation), (ii) failure of available seeds to reach recruitment sites (i.e., dispersal limitation), and (iii) failure of arrived seeds to establish at a location (i.e., establishment limitation). Here, we evaluated the relative importance of these mechanisms in three co‐occurring tree species ( Dipteryx oleifera, Attalea butyracea, and Astrocaryum standleyanum ) that share seed dispersers/predators. The study was set up on Barro Colorado Island (Panama) at 62 one‐ha sites with varying tree densities. Source limitation was estimated as the proportion of sites that would be reached by seeds if seeds were distributed uniformly. Dispersal limitation was estimated from the number of sites with seeds in the soil bank. Establishment limitation was evaluated by measuring germination and 1‐year survival in seed addition experiments. The effect of conspecific and heterospecific densities on the mechanisms was evaluated at three spatial scales (1, 5, and 9 ha). For all species, seed predation was the most important recruitment component (~80% decrease in seed survival). Establishment varied among species and was affected by conspecific and heterospecific species densities across spatial scales. Given that species identity, distribution, and seed dispersal/predation affect recruitment at multiple scales, multiscale studies are required to understand how recruitment limitation determines community structure in tropical forests. Abstract in Spanish is available with online material. Abstract : Recruitment limitation results from three mechanisms: (i) lack of seed sources (i.e., source limitation), (ii) failure of available seeds to reach recruitment sites (i.e., dispersal limitation), and (iii) failure of arrived seeds to establish at a location (i.e., establishment limitation). Here, we evaluated the relative importance of these mechanisms in three co‐occurring tree species ( Dipteryx oleifera, Attalea butyracea, and Astrocaryum standleyanum ) that share seed dispersers/predators. The study was set up on Barro Colorado Island (Panama) at 62 one‐ha sites with varying tree densities. For all species, seed predation was the most important recruitment component (~80% decrease in seed survival). Given that species identity, distribution and seed dispersal/predation affect recruitment at multiple scales, multiscale studies are required to understand how recruitment limitation determines community structure in tropical forests. Resumen: La limitación por reclutamiento, es decir, el fracaso de las especies para establecerse en un lugar disponible, es un potencial determinante de la estructura de las comunidades vegetales, provocando que las comunidades locales sean un subgrupo limitado del total de especies a nivel regional. La limitación por reclutamiento es el resultado de tres mecanismos: (i) falta de fuentes de semillas (i.e., limitación por fuentes), (ii) el fracaso de las semillas disponibles para llegar a lugares aptos para reclutamiento (i.e., limitación por dispersión), y (iii) el fracaso de las semillas que llegan a lugares disponibles para establecerse en esta ubicación (i.e., limitación por establecimiento). En este estudio, evaluamos la importancia relativa de estos mecanismos en tres especies de árboles que coexisten en el bosque tropical ( Dipteryx oleifera, Attalea butyracea y Astrocaryum standleyanum ), las cuales comparten dispersores/depredadores. Este estudio fue llevado a cabo en la Isla de Barro Colorado (Panamá) en 62 sitios de 1ha de tamaño y con variación en la densidad de arboles. La limitación por fuentes fue estimada como la proporción de sitios a los que podrían llegar las semillas si estas estuvieran distribuidas uniformemente. La limitación por dispersión, fue estimada a partir del numero de sitios con semillas en el banco de semillas. La limitación por establecimiento fue estimada midiendo, en experimentos de adición de semillas, la germinación y sobrevivencia después de un año. El efecto de la densidad de especies conspecíficas y heterospecíficas se evaluó a tres escalas espaciales (1, 5 y 9 ha). Para todas las especies, la depredación de semillas fue el mas importante componente de reclutamiento (~80% reducción de la sobrevivencia de las semillas). El establecimiento varió entres las especies y estuvo afectado por la densidad de especies conspecíficas y heterospecíficas a lo largo de multiples escalas espaciales. Teniendo en cuenta que la identidad de las especies, su distribución y la dispersión/depredación de semillas afectan el reclutamiento de especies a múltiples escalas, es importante realizar estudios a escalas múltiples para entender como la limitación por reclutamiento determina la estructura de los bosques tropicales.